Influence of silver diamine fluoride on the adhesive properties of interface resin-eroded dentin. (April 2021) - Cardenas, A.F.M.; Siqueira, F.S.F.; Morales, L.A.R.; Araujo, L.C.R.; Campos, V.S.; Bauer, J.R.; Reis, A.; Loguercio, A.D.
Abstract: Purpose: To evaluate the effects of silver diamine fluoride (SDF) on resin-eroded dentin bond strength (μTBS) and the in-situ degree of conversion (DC) for universal adhesives, and the chemical/morphological changes induced by SDF. Materials and methods: One hundred ten extracted molars were randomly assigned to 12 experimental groups: (1) SDF (eroded dentin [ED] without SDF, treatment with either 12% SDF [ED + 12%SDF], 38% SDF [ED + 38%SDF] or 38% SDF without iodide potassium [KI] [ED + 38% SDF Without KI]); (2) adhesive systems (Clearfil Universal Bond Quick and Scotchbond Universal Adhesive); (3) adhesive strategies (etch-and-rinse [ER] and self-etch [SE]). After restoration, the specimens were sectioned into resin-dentin sticks and the μTBS was evaluated. Selected sticks were used for DC evaluation via micro-Raman. The dentin-etching patterns and chemical/morphological changes induced by SDF were examined using energy dispersive X-ray spectroscopy (EDX-SEM). Data from the μTBS and DC tests for each adhesive were analyzed using two-way repeated measures ANOVA and Tukey's test (α = 0.05). Results: The application of SDF resulted in a higher μTBS compared to without SDF. However, a statistically significant difference was observed only when 38% SDF was applied (p < 0.001). The application of SDF did not significantly influence the mean DC for both adhesive systems (p > 0.61). EDX-SEM indicated the presence of silver ions in addition to calcium mineral deposition after SDF application. Additionally, the silver crystal deposition was found in the adhesive/hybrid layer, independent of the SDF concentration. No significant differences was observed when 38% SDF was applied with or without KI. Conclusion: The application of SDF to universal adhesives in the ER and SE modes may be a viable alternative to increasing the bonding to eroded dentin without jeopardizing the DC.